Integration of Translation and Semantics Studies in Arabic Language Learning at the Junior High School Level: A Descriptive Qualitative Analysis - Anisa Siti Muslimah; Mumu Muhlisin; Akmaliyah, Akmaliyah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Arabic language learning at the junior high school level has traditionally focused on grammar and vocabulary memorization, while the aspect of meaning or semantics is often overlooked. As a result, students tend to understand the language mechanically without grasping the communicative messages embedded in the text. This study aims to describe the forms, strategies, and benefits of integrating translation and semantics studies in Arabic language learning at the junior high school level. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, display, and verification to identify patterns of meaning integration in translation activities. The findings reveal that teachers link translation exercises with lexical and contextual meaning analysis, utilize narrative-dialogue texts, and conduct discussions on idiomatic meanings prior to translation. This approach enhances students’ ability to comprehend textual meaning, fosters semantic awareness, and motivates them, as the learning process becomes more logical and communicative. However, several challenges arise, including limited instructional time, varying levels of student proficiency, and insufficient teacher training in semantic linguistics. The study recommends the need for teacher training in the application of semantic theory and the development of meaning-based instructional materials, so that Arabic language learning at the junior high school level can be conducted more effectively, contextually, and meaningfully